Copper-supported catalyst, paint, air cleaning system, air cleaning method, and producing method of copper-supported catalyst
The copper-supported catalyst addresses the need for cost-effective alternatives to platinum by utilizing copper nanoparticles on titanium oxide carriers, providing efficient catalytic activity for air purification and self-cleaning applications.
Patent Information
- Application Number
- JP2023110879
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-01-20
AI Technical Summary
Existing semiconductor manufacturing processes face challenges with chemical contamination due to the use of expensive platinum-supported catalysts, which require frequent replacement and generate dust, and there is a need for cheaper alternatives with equivalent catalytic activity.
A copper-supported catalyst is developed, where copper nanoparticles are supported on anatase-type titanium oxide carriers with specific particle sizes, produced via a radiation method, offering high catalytic activity and reduced agglomeration.
The copper-supported catalyst achieves decomposition performance comparable to platinum-supported catalysts at a fraction of the cost, suitable for air purification systems and self-cleaning paints, reducing design complexity and maintenance efforts.
Smart Images

Figure 2025008597000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a copper-supported catalyst, a paint containing the copper-supported catalyst, an air purification system and an air purification method using the copper-supported catalyst, and a method for producing the copper-supported catalyst. [Background technology]
[0002] Semiconductor devices, displays, micromachines, thin coating films, etc. are manufactured in clean rooms where the number of particles in the gas, temperature, humidity, etc. are controlled during manufacturing and inspection. These products are processed while being controlled on the nano-level order, and in order to prevent adverse effects during processing, it is sometimes necessary to reduce the concentration of chemical substances in the atmosphere. For example, in the semiconductor manufacturing process, if a wafer is contaminated with chemical substances, it can affect the coatability of the resist, causing changes in the film thickness of the resist and the adhesion between the resist and the wafer, making it impossible to achieve the desired processing accuracy and resulting in a decrease in yield. When it is necessary to control the concentration of chemical substances in the atmosphere, chemical filters based on activated carbon are usually used. Because chemical filters adsorb chemical substances, they need to be replaced before they break through (the amount of adsorption is saturated), which requires time and cost to maintain, and there is also a risk of dust being generated during replacement.
[0003] The present inventors have reported that a hybrid catalyst in which platinum is supported on titanium dioxide pellets by impregnation can oxidize isopropyl alcohol to produce acetone as a secondary product without UV irradiation (Non-Patent Documents 1 and 2). In addition, the inventors have proposed a platinum-supported catalyst in which platinum nanoparticles are uniformly supported on the surface of a porous support, and an efficient photocatalyst that uses titanium dioxide as a porous support (Patent Document 1). These platinum-supported catalysts use small amounts of platinum because the platinum is supported as nanoparticles, but there is a demand for cheaper catalysts that do not use expensive platinum. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2022-019588 [Non-patent literature]
[0005] [Non-Patent Document 1] Maki Ichihara, Hirofumi Horada, Yoshihide Wakayama, Hironori Taki, Yuji Saito, "Possibility study of VOC decomposition using hybrid catalysts", Taisei Corporation Technology Center Report, No. 52 (2019) [Non-Patent Document 2] Maki Ichihara, Hirofumi Horada, Yoshihide Wakayama, Hironori Taki, Yuji Saito, "Examination of the possibility of VOC decomposition in a lightless environment using hybrid catalysts", Proceedings of the Architectural Institute of Japan, University Academic Lecture Series, 2019, p919-920 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a copper-supported catalyst having excellent catalytic activity, a paint containing the copper-supported catalyst, an air purification system using the copper-supported catalyst, an air purification method, and a method for producing the copper-supported catalyst. [Means for solving the problem]
[0007] The means for solving the problems of the present invention are as follows. [1]: A copper-supported catalyst, characterized in that copper nanoparticles are supported on the surface of an anatase-type titanium oxide support having a particle size of 3 nm to 15 nm. [2]: The copper-supported catalyst according to [1], characterized in that the amount of copper supported is 0.01% by weight or more and 1.0% by weight or less. [3]: A paint comprising the copper-supported catalyst according to [1] or [2]. [4]: An air purification system comprising a purification device that includes the copper-supported catalyst according to [1] or [2] and converts chemical substances in the air into other chemical substances. [5]: An air purification method comprising a step of converting chemical substances in the air into other chemical substances using the copper-supported catalyst according to [1] or [2]. [6]: A method for producing a copper-supported catalyst, comprising irradiating an aqueous liquid in which anatase-type titanium oxide particles having a particle size of 3 nm to 15 nm are dispersed and copper ions are dissolved, with ionizing radiation. Effect of the Invention
[0008] The copper-supported catalyst of the present invention has decomposition performance equal to or greater than that of a platinum-supported catalyst. Copper is approximately 1 / 4,000 the price of platinum, and the copper-supported catalyst of the present invention is much cheaper than conventional platinum-supported catalysts. The paint of the present invention can form a coating film having catalytic ability (decomposition ability), and can therefore be used as a paint for sick house syndrome and sick car countermeasures, a self-cleaning paint, etc. Since the shape of the object to which the paint of the present invention is applied is not limited, when designing an exhaust air purification system or the like that is provided with a coating film coated with the paint of the present invention, the effort required for designing the internal structure to optimize pressure loss and decomposition can be significantly reduced. The method for producing a copper supported catalyst of the present invention, which is a radiation method, can produce a copper supported catalyst without going through a drying state during the process. Since the copper supported catalyst is less likely to aggregate, the production method of the present invention is particularly suitable for using the resulting catalyst in paint applications. [Brief description of the drawings]
[0009] [Figure 1] Graph showing the ratio of isopropyl alcohol (IPA) and acetone (ACT) and carbon dioxide (CO2) produced by decomposition of IPA after an isopropyl alcohol decomposition test in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Copper-supported catalyst The copper supported catalyst (hereinafter also referred to as the catalyst) of the present invention has copper nanoparticles supported on the surface of an anatase type titanium oxide support having a particle size of 3 nm or more and 15 nm or less. The catalyst of the present invention uses anatase type titanium oxide having a particle size of 3 nm to 15 nm as a carrier. The particle size of the carrier is more preferably 4 nm, even more preferably 5 nm or more, more preferably 13 nm or less, even more preferably 11 nm or less, and even more preferably 9 nm or less. In this specification, the particle size of the carrier is the crystallite diameter (also called crystallite size), which is a value calculated using the Scherrer formula below from the half-width of the peak obtained by powder X-ray diffraction. Lc=0.9λ / (w cosθ) (Lc: crystallite size (nm), λ: X-ray wavelength (nm), w: peak half-width (rad), θ: angle of peak position.)
[0011] In the catalyst of the present invention, the particle size (area circle equivalent diameter) of the copper nanoparticles can be obtained by image processing of an electron microscope image obtained by imaging a sample and calculating the area circle equivalent diameter. In the catalyst of the present invention, of 100 or more copper nanoparticles obtained by image processing of an electron microscope image, those with a particle size (area circle equivalent diameter) of 2 nm or less are preferably 90% or more, more preferably 95% or more, even more preferably 99% or more, and most preferably 100%.
[0012] The catalyst of the present invention is a photocatalyst using anatase-type titanium oxide as a carrier. The catalyst of the present invention has high catalytic activity, although the mechanism is unclear, compared with copper-supported catalysts using a particle size outside the range of the present invention and a type of carrier outside the range of the present invention (e.g., rutile-type titanium oxide). The copper-supported catalyst of the present invention can be used in decomposition reactions of various chemical substances, and can be suitably used, for example, in decomposition reactions for converting ethanol, isopropyl alcohol, ethyl acetate, propylene glycol monomethyl ether (PGME), propylene glycol monomethyl ether acetate (PGMEA), toluene, ammonia, etc., into other chemical substances that are intermediate products or final products (water, carbon dioxide, etc.).
[0013] ·Manufacturing method The copper-supported catalyst of the present invention can be produced, for example, by a radiation method. The radiation method is a method in which an aqueous metal ion solution (a copper ion solution in the present invention) in which a carrier is dispersed is irradiated with radiation, the metal ions are reduced by reducing species generated by radiolysis of water to precipitate nanoparticles, and the precipitated nanoparticles are supported on the carrier. Nanoparticles are uniformly precipitated by the radiation method, and the precipitated nanoparticles are uniformly supported on the surface of the carrier. The radiation method can produce a copper-supported catalyst without going through a drying state, so the copper-supported catalyst is less likely to aggregate and is easy to maintain a dispersed state.
[0014] When produced by the radiation method, the catalyst of the present invention can be produced by irradiating an aqueous liquid in which anatase type titanium oxide having a particle size of 3 nm or more and 15 nm or less is dispersed and copper ions are dissolved, with ionizing radiation. The ionizing radiation used is not particularly limited, but in view of transparency and safety, it is preferable to use gamma rays, X-rays, or electron beams. When gamma rays are used as the ionizing radiation, the gamma rays are preferably irradiated under conditions of a dose of 1 kGy to 100 kGy, more preferably 10 kGy to 40 kGy. A preferred specific example of gamma ray irradiation is a radiation source using a cobalt 60 gamma ray source (energy of gamma ray photon: 1.25 MeV), at a dose rate of about 3 kGy / h, and for an irradiation time of 1 to 18 hours. When an electron beam is used as the ionizing radiation, the acceleration energy of the electron beam is preferably 0.1 MeV to 10 MeV, more preferably 1 MeV or more. The absorbed dose in the irradiation of the electron beam is preferably 1 kGy to 100 kGy, more preferably 10 kGy to 40 kGy.
[0015] The amount of copper supported in the catalyst of the present invention can be adjusted by the copper ion concentration, radiation intensity, radiation exposure time, carrier concentration, etc. The amount of copper supported in the copper-supported catalyst of the present invention is not particularly limited as long as the effects of the present invention are achieved, but is preferably 0.01% by weight or more and 1.0% by weight or less. The amount of copper supported is more preferably 0.05% by weight or more, even more preferably 0.1% by weight or more, more preferably 0.8% by weight or less, and even more preferably 0.6% by weight or less.
[0016] ·paint The coating material of the present invention contains the copper-supported catalyst described above. When the catalyst of the present invention is produced by the radiation method, an aqueous dispersion in which the copper-supported catalyst is dispersed in an aqueous medium is obtained, and this aqueous dispersion can also be used as a paint as it is. The copper-supported catalyst produced by the radiation method has excellent dispersibility, making it suitable for paint applications. In addition, dispersants, inorganic binders such as hydrolyzable alkoxysilanes, water-soluble organic solvents such as ethanol and isopropanol, etc. can be added to this aqueous dispersion, and dilution, concentration, solvent replacement, etc. can also be performed. The catalyst of the present invention is a nanoparticle supported by anatase-type titanium oxide having a particle size of 3 nm to 15 nm. In order to prevent the aggregation of the catalyst, which is a nanoparticle, the solvent of the paint is preferably an aqueous medium containing water. The coating material of the present invention can form a coating film having catalytic ability (decomposition ability), and is therefore suitable as a coating material for preventing sick house syndrome and sick car syndrome, a self-cleaning coating material, and the like.
[0017] Air Purification System The air purification system of the present invention includes a purification device that includes a copper-supported catalyst in which copper nanoparticles are supported on the surface of an anatase-type titanium oxide support having a particle size of 3 nm or more and 15 nm or less, and that converts chemical substances in the air into other chemical substances. By using a paint containing the catalyst of the present invention, a coating film having catalytic activity can be formed on the surface of any article. For example, a purification device can be created by simply forming a coating film inside an existing exhaust pipe, etc., and installing a light source that irradiates the coating film with ultraviolet light. Compared to conventional filter-like catalysts that are installed to hinder the flow of gas, the coating film and light source do not hinder the flow of gas, so there is no large pressure loss, and the internal design of the air purification device and air purification system can be simplified.
[0018] The chemical substances to be treated by the air purification system of the present invention are not limited as long as they are organic compounds that can be decomposed by the copper-supported catalyst used. When the other chemical substances produced by the purification device equipped with the copper-supported catalyst are intermediate products, the air purification system of the present invention can have a second purification device equipped with a photocatalyst or the like that decomposes the intermediate products into final products containing carbon dioxide and water downstream of the purification device. EXAMPLES
[0019] "Example 1" 3.33 g (equivalent to 1 g of titanium oxide) of an aqueous dispersion of anatase-type titanium oxide (Ishihara Sangyo Kaisha, Ltd., STS-01, titanium oxide concentration 30 wt%, X-ray particle size 7 nm) was taken, 0.2 mmol of copper nitrate and 2 mL of isopropyl alcohol were added, and ultrapure water was added to adjust the total liquid volume to 200 mL to prepare the starting aqueous solution. In this solution, copper is 0.13 wt% relative to the weight of titanium dioxide. The starting aqueous solution was placed in a glass container and bubbled with argon gas for 15 minutes to remove dissolved oxygen, and then the container was sealed. Then, 40 kGy of gamma rays were irradiated using a cobalt 60 gamma ray source to obtain a copper-supported catalyst dispersed in water.
[0020] "Comparative Example 1" A platinum-supported catalyst dispersed in water was obtained in the same manner as in Example 1, except that an aqueous solution containing platinum ions (HPtCl: 1 mM, isopropyl alcohol: 1 vol%) was used. The amount of platinum relative to the weight of titanium dioxide was 0.2% by weight. "Comparative Example 2" A copper-supported catalyst dispersed in water was obtained in the same manner as in Example 1, except that an aqueous dispersion of rutile-type titanium oxide (Sakai Chemical Industry Co., Ltd., SRD-W, X-ray particle size 5 nm) was used. The amount of copper relative to the weight of titanium dioxide was 0.13% by weight.
[0021] "Comparative Example 3" A copper-supported catalyst dispersed in water was obtained in the same manner as in Example 1, except that an aqueous dispersion of anatase-type titanium oxide (Ishihara Sangyo Kaisha, Ltd., ST-21, X-ray particle size 20 nm) was used. The amount of copper relative to the weight of titanium dioxide was 0.13% by weight. "Comparative Example 4" A copper-supported catalyst dispersed in water was obtained in the same manner as in Example 1, except that an aqueous dispersion of rutile-type titanium oxide (Sakai Chemical Industry Co., Ltd., STR-100N, X-ray particle size 16 nm) was used. The amount of copper relative to the weight of titanium dioxide was 0.13% by weight.
[0022] ·Coating film formation A hydrophilic undercoat material (CARMATE EXCLEAR Superhydrophilic Coat for Mirrors) was applied to a plate glass (100 mm x 20 mm x 2 mm) to form a base. 200 μl of each of the aqueous dispersions of the copper-supported catalyst and platinum-supported catalyst obtained in Example 1 and Comparative Examples 1 to 4 was applied onto the base as is as paint, and the resulting mixture was naturally dried for 24 hours to form a coating film containing the copper-supported catalyst or platinum-supported catalyst. In addition, as a reference example, a coating film was formed using a titanium dioxide dispersion that was the same as the starting aqueous solution used in Example 1, except that copper nitrate was not added, as paint.
[0023] ·IPA decomposition The glass plate with the coating film formed thereon was placed in a 122 ml quartz vial, and 0.5 μL of isopropyl alcohol (IPA) (IPA concentration in the vial: 1276 μmol / L) was poured in and the glass plate was sealed. UV (253.7 nm) was irradiated toward the coated surface of the glass plate for 15 minutes. After 15 minutes, UV irradiation was stopped, and the gas in the vial was extracted with a syringe, and the isopropyl alcohol (IPA) concentration, acetone (ACT) concentration, and carbon dioxide concentration were measured using a gas chromatograph (Shimadzu Corporation, GC-2014, detector FID). The carbon dioxide concentration after 24 hours was calculated with the initial carbon dioxide concentration set to 400 ppm. The ratio of each substance was calculated from the concentration of each substance. Since one molecule of isopropyl alcohol produces one molecule of acetone and three molecules of carbon dioxide, the ratio of carbon dioxide was calculated by setting the carbon dioxide concentration to 1 / 3. The results are shown in Table 1 and Figure 1.
[0024] [Table 1]
[0025] The carbon dioxide ratio in Example 1, in which the copper-supported catalyst of the present invention was used, was 50.8%, which was higher than the carbon dioxide ratio of 30.0% in Comparative Example 1, in which the platinum-supported catalyst was used. The copper-supported catalyst of the present invention had a higher decomposition activity than the platinum-supported catalyst. It was confirmed from Example 1 and Comparative Examples 2 to 4 that when anatase-type titanium oxide having a particle size of 3 nm or more and 15 nm or less is used as a support, a copper-supported catalyst having excellent decomposition activity can be obtained.
Claims
1. A copper-supported catalyst, comprising copper nanoparticles supported on the surface of an anatase-type titanium oxide support having a particle size of 3 nm to 15 nm.
2. 2. The copper supported catalyst according to claim 1, wherein the amount of supported copper is 0.01% by weight or more and 1.0% by weight or less.
3. A paint comprising the copper supported catalyst according to claim 1 or 2.
4. 3. An air purification system comprising a purification device comprising the copper supported catalyst according to claim 1 or 2, and converting chemical substances in the air into other chemical substances.
5. 3. An air purification method comprising a step of converting chemical substances in the air into other chemical substances by using the copper supported catalyst according to claim 1 or 2.
6. A method for producing a copper-supported catalyst, comprising irradiating an aqueous liquid having dispersed therein anatase-type titanium oxide particles having a particle size of 3 nm to 15 nm and having copper ions dissolved therein, with ionizing radiation.
Citation Information
Patent Citations
Platinum-supported catalyst, air cleaning system and air cleaning method
JP2022019588A